2012
DOI: 10.1186/1746-6148-8-228
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the occurrence and level of Isospora suis oocyst excretion in nursing piglets of Greek farrow-to-finish herds

Abstract: BackgroundPiglet isosporosis is one of the most common parasitic diseases in modern pig production. To prevent clinical disease, prophylactic treatment of piglets with toltrazuril (BAYCOX® 5%, Bayer HealthCare, Animal Health, Monheim, Germany) is widely practiced in the past 20 years. There are only very few reports documenting the likely effect of managerial practices, such as hygiene measures, all-in-all-out management of farrowing facilities and piglet manipulations, and/or farm-specific environment - i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In this multicenter study C. suis infection rates varied considerably between farms (38.5% (HP1) to 97.0% (GC1) of untreated controls). Such variations were reported earlier and obviously correspond to farm management and hygiene measures ( Aliaga-Leyton et al, 2011 , Skampardonis et al, 2012 ). Regional aspects may also have an impact on coccidiosis prevalence ( Meyer et al, 1999 ).…”
Section: Discussionsupporting
confidence: 71%
“…In this multicenter study C. suis infection rates varied considerably between farms (38.5% (HP1) to 97.0% (GC1) of untreated controls). Such variations were reported earlier and obviously correspond to farm management and hygiene measures ( Aliaga-Leyton et al, 2011 , Skampardonis et al, 2012 ). Regional aspects may also have an impact on coccidiosis prevalence ( Meyer et al, 1999 ).…”
Section: Discussionsupporting
confidence: 71%
“…Finally, this approach is also useful for parasitic diseases and, for example, if cross-fostering was either not applied or was carried out only during the first 24 hours of life in a herd decrease the possibility of Isospora suis oocyst excretion versus herds in which the cross-fostering of piglets after day one of life was commonly carried out. Moreover, it has been observed that cross-fostered piglets may shed earlier this parasite and may be responsible for litter contamination 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Coccidiosis transmission occurs in faeces and the disease is difficult to control in outdoor herds where it is difficult to prevent contact with faeces (Skampardonis et al, 2012). This was the only vaccination or medication variable that was significantly associated with piglet mortality in the final model.…”
Section: Discussionmentioning
confidence: 99%